Socio-demographic vulnerability : old and new risks for communities; households and individuals : summary and conclusions (ECLAC SantiagoCL, 2002)
Aims to apply a vulnerability-oriented approach to the analysis of the relations between population and development at the community, household and personal levels.
Bibliography: p. 29-34